Prevalence of MRSA (Methicillin-Resistant Staphylococcus Aureus) in Burn Wound Infections and its Antibiotic Susceptibility Patterns - Zubeda Irshad, Mahnoor Khan, Rabbia Mahboob, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Burn injuries provide an ideal environment for bacterial colonization and infection, particularly by resistant strains such as methicillin-resistant Staphylococcus aureus (MRSA). Once established, MRSA infections can delay wound healing, prolong hospitalization, and increase the risk of sepsis and mortality. This study aimed to determine the prevalence of MRSA among burn wound infections and to assess the antibiotic susceptibility patterns of the isolates. Methods: A descriptive cross-sectional study was conducted over two year, from January 2020 to December 2021, involving 751 isolates of Staphylococus aureus from burn patients in a tertiary care burn hospital. Wound swabs from clinically infected burn sites were cultured and analyzed for bacterial identification. MRSA was detected using cefoxitin disc diffusion method, and antibiotic susceptibility testing was performed using the Kirby-Bauer disc diffusion technique according to Clinical and Laboratory Standards Institute (CLSI) guidelines. Results: Out of 751 Staphylococcus aureus isolates from burn patients, 421 (56%) were identified as methicillin-resistant Staphylococcus aureus (MRSA), while 330 (43.9%) were methicillin-sensitive S. aureus (MSSA). MRSA infections were significantly associated with larger total body surface area (TBSA) burns, ICU admissions, prior antibiotic use, and the presence of comorbidities (p< 0.05). Antibiotic susceptibility testing showed 99.6% sensitivity to vancomycin and 91.7% to linezolid. Resistance was highest against trimethoprim-sulfamethoxazole (TMP-SMX) (99.6%), ciprofloxacin (95.8%), and clindamycin (87.5%). Amikacin and tetracycline demonstrated limited effectiveness, with sensitivity rates of 29.2% and 16.7%, respectively. Conclusion: MRSA remains a prevalent and clinically significant pathogen in burn wound infections, especially among patients with extensive burns, prior antibiotic exposure, ICU admissions, and comorbidities. Vancomycin (99.6% sensitivity) and linezolid (91.7%) continue to be the most effective therapeutic options against MRSA in this setting. The high resistance to commonly used antibiotics such as TMP-SMX, ciprofloxacin, and clindamycin underscores the urgency for routine microbiological surveillance, judicious antibiotic prescribing, and strict infection control measures. Implementing targeted antimicrobial stewardship and evidence-based protocols is essential to curb the spread of multidrug-resistant organisms in burn care units. Keywords: MRSA, burn wound infection, antibiotic resistance, Staphylococcus aureus, susceptibility pattern, vancomycin, amikacin, infection control.